IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN HASIL BELAJAR SISWA DI KELAS IV SDN 09 SUNGAI KELAMBU TAHUN PELAJARAN 2023-2024 - Sofia; Yayan Ridwan; Nurlisa (JIP: Jurnal Ilmu Pendidikan, 2026)
The purpose of this study was to reveal: 1). Teacher planning in implementing the independent curriculum on student learning outcomes in Class IV SDN 09 Sungai Kelambu in the 2023-2024 academic year; 2). Teacher implementation in implementing the independent curriculum on student learning outcomes in class IV SDN 09 Sungai Kelambu in the 2023-2024 academic year; 3). evaluation of the implementation of the independent curriculum on student learning outcomes in class IV SDN 09 Sungai Kelambu in the 2023-2024 academic year This study uses a qualitative approach with a phenomenological research type. Data collection techniques use interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study show that; 1. Teacher planning in implementing the independent curriculum on student learning outcomes in grade IV of SDN 09 Sungai Kelambu in the 2023-2024 academic year, namely the preparation of learning objectives, selection of methods, development of teaching materials, and preparation of teaching modules are carried out systematically and integrated with the Independent Curriculum and the Pancasila student profile. The main focus is the development of student competencies in knowledge, skills, and attitudes through a relevant, contextual, and needs- and interests-oriented approach, ensuring active involvement and effective learning. 2. Teacher implementation in implementing the independent curriculum on student learning outcomes in grade IV of SDN 09 Sungai Kelambu in the 2023-2024 academic year, namely creativity and innovation in teaching, a student-centered approach, use of technology, learning media and character building are effectively implemented. The learning process involves creative methods, consistent technology, and moral values, with teachers acting as facilitators, ensuring students are actively involved and important values ​​are integrated into everyday life. 3. Evaluation of the Implementation of the Independent Curriculum on Student Learning Outcomes in Class IV of SDN 09 Sungai Kelambu in the 2023-2024 Academic Year, namely student learning outcomes are evaluated comprehensively through formative and summative methods, with feedback used to improve teaching effectiveness. In addition, regular communication between teachers and parents, both in person and online, ensures involvement and support in the educational process.